Do Loan Service Quality and Loan Administrative Satisfy? - Cristine Supone; Cepi Pahlevi; Muhammad Sobarsyah (Magister Management, Hasanuddin University, 2022)
This study aims to determine the effect of loan service quality and administrative loan procedures (KUR) on customer satisfaction at PT. Bank BNI Regional Office 07 Makassar. The study uses a sample of 100 respondents using a questionnaire. Data collected is then analyzed using multiple linear regression. The result of the study indicated that the service quality satisfied loan customers. Differently, administrative micro-loan did not show a significant relationship, suggesting it did not affect the administrative loans on customer satisfaction.